Sustainability in Dentistry: A Multifaceted Approach Needed. (August 2020) - Duane, B.; Stancliffe, R.; Miller, F.A.; Sherman, J.; Pasdeki-Clewer, E.
This article provides an introduction to environmentally sustainable dentistry and offers perspectives on managing drivers to reduce carbon emissions and make dentistry more environmentally sustainable. A sustainable world must meet the needs of the present without compromising the ability of future generations to meet their own needs. Global commitment to sustainability and demands for a sustainable world are growing. Within dentistry, travel creates the highest carbon emissions and also contributes to human health damage. Internally, there are a number of ways to reduce impact by decreasing travel and energy use, as well as carefully considering the types of items purchased (and how they are disposed of). Larger dental organizations can influence their suppliers and industry by choosing to purchase from sustainable companies with environmentally friendly products. From an external driver perspective policy, guidance and research are essential. Governments need to reevaluate decontamination policy from an environmental perspective. Decontamination documents need revision to consider both planetary and public health. Dental organizations need to support dental teams in this area. Insurance providers and health care purchasers should review policies to influence the sustainability of dental providers. Sustainability education needs to be considered as part of the curriculum of undergraduate and postgraduate students. Guidance could also be developed for the dental industry to produce sustainable products. Research needs to be prioritized. Identifying hot spots or areas of high environmental contributions using other assessments such as life cycle analysis (LCA) would allow dentistry to identify products or practices that have a disproportionate adverse impact on the environment and might be prioritized for change. This should include an analysis of single-use instruments, chemicals, and products. Building research capacity by training students and creating virtual or physical centers for sustainability is essential. Financial support is needed for priority areas of research.